Cloud removal from satellite imagery based on SUSAN algorithm - LU Li1; WANG Yong-tao1; TIAN Jin-wen1; LIU Jian1 (Tongxin xuebao)
A new image fusion scheme that could automate remove the cloud covers in the main image was proposed based on SUSAN algorithm.First,the corners were found both in the main image and the reference image based on SUSAN algorithm,and then the matched corners were found using probabilistic relaxation algorithm to register the ref-erence image to the main image.Finally,a cloud-removed image was obtained by fusion.The performance of the pro-posed scheme is demonstrated experimentally.